1993
DOI: 10.1159/000126465
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Altered Thyroid States on 5-HT<sub>1A</sub> Receptors and 5-HT Uptake Sites in Rat Brain: An Autoradiographic Analysis

Abstract: Although a link between the hypothalamic-pituitary-thyroid (HPT) axis and affective disorder has been established, the mechanism underlying this relationship remains unclear. Since the serotonin (5-HT) system appears to be involved in the pathophysiology of mood disorders, the time course of the effects of thyroidectomy (TXT) with or without thyroxine (T4) replacement on 5-HT1a receptors and 5-HT uptake sites was examined. TXT caused a significant increase in 3H-8-hydroxy-2-(di-n-propylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
2
27
1
2
Order By: Relevance
“…Studies on the density of 5-HT 1A (postsynaptic) receptors outside the brainstem yielded contradictory results. An increase in cortical and hippocampal 5-HT 1A (postsynaptic) receptors was observed by Tejani-Butt et al 50 but not by Hong et al 49 and Kulikov et al, 51 who found no significant differences compared to euthyroid adult rodents.…”
Section: Measurements Of 5-ht and Its Metabolites In Adult Hypothyroimentioning
confidence: 86%
See 1 more Smart Citation
“…Studies on the density of 5-HT 1A (postsynaptic) receptors outside the brainstem yielded contradictory results. An increase in cortical and hippocampal 5-HT 1A (postsynaptic) receptors was observed by Tejani-Butt et al 50 but not by Hong et al 49 and Kulikov et al, 51 who found no significant differences compared to euthyroid adult rodents.…”
Section: Measurements Of 5-ht and Its Metabolites In Adult Hypothyroimentioning
confidence: 86%
“…In experimentally-induced hypothyroid states the 5-HT 1A (presynaptic) receptor density in the brainstem and midbrain was not altered [49][50][51][52] (Table 1). Studies on the density of 5-HT 1A (postsynaptic) receptors outside the brainstem yielded contradictory results.…”
Section: Measurements Of 5-ht and Its Metabolites In Adult Hypothyroimentioning
confidence: 99%
“…Although there is evidence that thyroid hormones selectively regulate a limited set of genes, the direct targets of thyroid hormone action have not unambiguously been identified (Oppenheimer et al 1994). Thyroid hormones have been shown to influence the expression of a variety of transporters, enzymes and receptors involved in transmitter uptake, metabolism and detection (Honegger & Lenoir 1980 ;Patel et al 1980 ;Atterwill et al 1984 ;Dussault & Ruel 1987 ;Tejani-Butt et al 1993) of some cytoskeletal proteins (e.g. Aniello et al 1991) and neurotrophins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In hypothyroid rats there are was a marked decrease of NE and DA as well as 5HT contents in most of the brain area examined (Table 2-5). Brain serotonin synthesis and turnover in rats was decreased in the sensitivity of serotonin receptors (Vaccari, 1982) and compensatory increase in the density of 5HT receptors, secondary to reduction in the level of synaptic serotonin (Tejani-Butt et al, 1993). Immunohistochemical studies in animal brains showed that T3 has high concentration in sinaptosomes, especially those located in noradrenergic neurotransmission brain nuclei (Dratman and Gordon, 1996).…”
Section: Discussionmentioning
confidence: 99%